Is there a correlation between vitiligo and hearing loss? - review of the literature - Rusinowska, Barbara (Journal of Education, Health and Sport, 2022)
Vitiligo is the most common cause of hipopigmentation occuring with a frequency of 0.5-2% relying on impairment of melanin production caused by the loss of melanocytes. Melanocytes are observed not only in the skin’s epidermis and hair follicles but also in the mucosa, the uvea, mesencephalon and on the structures of inner ear – including the stria vascularis, the cochlea and the dark cell areas in the vestibular organs where they play role in regulation auditory and equilibrium functions. These rationale prompted scientists to study the link between hearing loss and vitiligo. Scientists’ opinions are divided in this respect - some of them, as a result of their research, see a possible connection, others do not see a correlation between the two diseases. In this review, we present the latest studies evaluating the correlation of hearing impairment with vitiligo.